How have the strategies of Airlines been affected by the 2008 economic recession? A study focusing on British Airways, American Airlines, Southwest Airlines and EasyJet. - Morley, Christopher M (2009)
Abstract This paper looks at both Porters Generic strategies theory and the newer resource based view of strategy and applies these theories to the Airline industry using four focus cases. The companies looked at are British Airways, EasyJet, Southwest Airlines and American Airlines. The study of these cases allows for an overview of the role of strategy in the airline industry and enables a comparison regarding the effects of the current economic recession on the chosen airlines and the markets in which they operate. This allows for a comparative analysis to be carried out on the effectiveness of the individual strategies adopted by each case. The literature review looks at current theories regarding strategy and its application to the Airline industry. The methodology used is case study research which allows for a detailed look at the chosen companies. The cross case analysis looks and the relative strategic positions that the chosen cases have found themselves in. The conclusions reached indicate that the main problem for airlines is the price of oil and intense competition. LCCs are in a much stronger position within their respective markets than traditional carriers. The main future strategy for traditional carriers will be the adoption of alliances which gives member airlines a unique competitive advantage whilst LCCs may want to examine the possibility of long-haul routes in order to continue their growth.